The New Integrative Method Of Psychotherapie «Inoculation Against Suggestion» - Prostomolotow, V. F. (Psychiatry, Neurology and Medical Psychology, 2016)
It’s rnown, to particulary experienced psychotherapist and narcologist, what exposuring at patients high suggestibility predetermines in many cases, in spite of rapid effect, of short duration success of medical. The complaisan to negativ extenal or internal suggestibility influence is heightened, but doctor cannot be perma-nent near. We devise and effective employ about many years the method “Inocula-tion against suggestion” in forme of two modes, when take that into account.